Use of the sensors of a latest generation mobile phone for the three-dimensional reconstruction of an archaeological monument: The survey of the Intihuatana stone in Machu Picchu (Peru') - Baiocchi, Valaerio (2020)
The survey of archaeological monuments presents particular needs and difficulties. Such surveys must in fact be as complete, geometrically correct and accurately geo-referenced as possible. These needs, however, often face problems of difficult accessibility, the need for rapid timing and complex logistical conditions. The latest generation of mobile phones are equipped with ultra-high resolution cameras up to 100 megapixel. Although they do not have the geometric characteristics of professional cameras, they can be used advantageously for the reconstruction of three-dimensional models using Structure from Motion methodologies . At the same time, the latest mobile phones are equipped with GPS/GNSS chips that allow a postprocessing of their positioning allowing to reach decimetric/centimetric accuracies. The use of sensors integrated in a mobile phone greatly simplify the survey both in terms of transportability but also in terms of authorizations by the competent authorities as the equipment is exactly the same that most tourists who visit the sites themselves bring with them. The approach proposed and made possible by these combined features in a latest generation mobile phone have been tested for a rapid survey of the Intihuatana stone in Machu Picchu (Peru), a site with considerable logistical and organizing complexity.